Acute Arthritis in Children: How to Discern between Septic and Non-Septic Arthritis? - Lisa Gamalero; Giovanna Ferrara; Teresa Giani; Rolando Cimaz (MDPI AG, 2021)
The term septic arthritis refers to an infection of the synovial space. This is an infrequent condition in healthy children, but it should be considered a medical emergency potentially leading to irreversible articular damage. Therefore, prompt diagnosis and antimicrobial treatment play a crucial role in improving the prognosis. Although septic arthritis is the most common cause of acute arthritis, many other diseases may mimic a similar clinical picture, constituting a diagnostic challenge for the clinician who first approaches the patient. Herein we analyze the main features of septic arthritis, offering an overview of the main conditions involved in the differential diagnosis and suggesting a diagnostic workup plan.